Dual model describing effects of evaporated metal gate on low-k dielectric methylsilsesquioxane in metal oxide semiconductor capacitor structure - Aw, K.C.; Ibrahim, K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Spin-on Methylsilsesquioxane (MSQ) exhibits low dielectric constant and is an important and promising material to reduce parasitic capacitive coupling between metal layers in semiconductor integrated circuits. However, MSQ has lower film density and therefore more porous than the traditional silicon dioxide (SiO₂) film and could pose reliability issues. This paper is an extension to previous paper [1], which reported that evaporated copper (Cu) onto spin-on MSQ has high leakage current and provides two alternative models with the aid of energy band diagrams to describe the effect of evaporated Cu onto spin-on MSQ using Metal Oxide Semiconductor capacitor (MOSC) structure.